2003
DOI: 10.1016/s0160-4120(02)00063-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of sensory irritants in indoor air—a case study in a French school

Abstract: Exposure to airborne pollutants can result in adverse health effects. Acute symptoms can for instance comprise of irritation of the eyes or of the respiratory tract (called sensory irritation). In a recent case, health problems were reported in a French school and supposedly attributed to the presence of airborne irritant pollutants. Based on measured concentrations, the risk of developing the described health effects was assessed.Numerous airborne sensory irritants (aldehydes, organic acids, VOCs, SO 2 , NH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The most frequent symptoms listed on the questionnaires were related to respiratory problems such as flu, bronchitis, rhinitis, tonsillitis, irritation of throat, nose, and epidemic conjunctivitis. All of these symptoms are known to be related to IAQ (Meininghaus et al 2003). Some published data on the level of indoor and outdoor pollutants in Korea were similar to this study (Baek et al 1997;Jo et al 2003) while others are somewhat higher (Bae et al 2004;Son et al 2003) depending on the sampling protocol, local area and year.…”
Section: Discussionsupporting
confidence: 81%
“…The most frequent symptoms listed on the questionnaires were related to respiratory problems such as flu, bronchitis, rhinitis, tonsillitis, irritation of throat, nose, and epidemic conjunctivitis. All of these symptoms are known to be related to IAQ (Meininghaus et al 2003). Some published data on the level of indoor and outdoor pollutants in Korea were similar to this study (Baek et al 1997;Jo et al 2003) while others are somewhat higher (Bae et al 2004;Son et al 2003) depending on the sampling protocol, local area and year.…”
Section: Discussionsupporting
confidence: 81%
“…In another study by Meininghaus et al (2003), sensory irritation was reported in school children. The airborne levels of several respiratory irritants were measured (e.g., SO 2 , ammonia, acetic acid, formic acid, hexanal, butanal, acetaldehyde, and formaldehyde).…”
Section: Iiisensory Irritationmentioning
confidence: 90%
“…Other studies focussed on the relation between pollution and health outcomes. Meininghaus et al. (2003) organized a study aimed at identifying compounds (aldehydes, organic acids, volatile organic compounds, SO 2 and NH 3 ), which could be responsible for the reported adverse health effects, but no cause could be identified.…”
Section: Introductionmentioning
confidence: 99%